SPECIFICITY OF DESIGN AND PROMOTION OF THE VEGETARIAN RESTAURANTS AS AN APPROACH TO IMPROVE THE COMPETITIVENESS OF THE DESTINATION - V. Alieva; A. Savtcova; L. Alieva (Вестник Северо-Кавказского федерального университета)
The objective of this research work is to study the best international practices of designing and promoting vegetarian healthy food restaurants. It is based on the complex analysis of the theoretical material and experimental research, comprising consumer market analysis, the choice of the restaurant location (advantages and disadvantages), analysis of the competitive environment (SWOT analysis of competitors), technological and product design, development of vegetarian menu, selection of service system. The project resulted in the development of a medium-term plan for promoting the restaurant «S&M» and for embedding the project «S&M» into the development programme of Stavropol as a tourist destination.